THE INFLUENCE OF WORK MOTIVATION, INCENTIVES AND CONTRACT WORK SYSTEM ON EMPLOYEE PERFORMANCE PT. PHAROS INDONESIA SURABAYA BRANCH - Kurniawati, Ony; Pelitawati, Dyah; Taufan Arliansyah, Dimas (Sekolah tinggi ilmu ekonomi pemuda, 2023)
This study aims to test and analyze the effect of Work Motivation, Incentives, and Contract Work System on Employee Performance of PT Pharos Indonesia Surabaya branch. From this goal, PT Pharos Indonesia continues to strive to develop and improve the human resources in it including the excellence of its professionalism. This study uses quantitative data types where the sample used is all employees of PT Pharos Indonesia Surabaya branch totaling 35 contract employees of the marketing division. The measurement technique between variables is to use the Likert Scale in the questionnaire. The results of the analysis of this study indicate that partially the variables of Work Motivation, Incentives, and Contract Work System have a significant effect on Employee Performance. Simultaneously the variables of Work Motivation, Incentives, and Contract Work System have a significant effect on the Employee Performance variable, with a significant value of 0.000.